Utility of Peripheral Visual Cues in Planning and Controlling Adaptive Gait - Graci, Valentina; Elliott, David B.; Buckley, John G. (Optometry and vision science, 2010)
To determine the relative importance to adaptive locomotion of peripheral visual cues provided by different parts of the visual field. Twelve subjects completed obstacle crossing trials while wearing goggles that provided four visual conditions: upper visual field occlusion, lower visual field occlusion (LO), circumferential peripheral visual field occlusion (CPO), and full vision. The obstacle was either positioned as a lone structure or within a doorframe. Given that subjects completed the task safely without cues from the lower or peripheral visual field, this suggests that subjects used exteroceptive information provided in a feed-forward manner under these conditions. LO and CPO led to increased foot placement distance from the obstacle and to increased toe clearance over the obstacle with a reduced crossing-walking velocity. The increased variability of dependent measures under LO and CPO suggests that exproprioceptive information from the peripheral visual field is generally used to provide online control of lower limbs. The presence of the doorframe facilitated lead-foot placement under LO by providing exproprioceptive cues in the upper visual field. However, under CPO conditions, the doorframe led to a further reduction in crossing velocity and increase in trail-foot horizontal distance and lead-toe clearance, which may have been because of concerns about hitting the doorframe with the head and/or upper body. Our findings suggest that exteroceptive cues are provided by the central visual field and are used in a feed-forward manner to plan the gait adaptations required to safely negotiate an obstacle, whereas exproprioceptive information is provided by the peripheral visual field and used online to "fine tune" adaptive gait. The loss of the upper and lower peripheral visual fields together had a greater effect on adaptive gait compared with the loss of the lower visual field alone, likely because of the absence of lamellar flow visual cues used to control egomotion.